2013
DOI: 10.1002/rra.2691
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Thermal Regime Alteration and Spawning Delay of the Four Major Chinese Carps in the Yangtze River Below the Three Gorges Dam

Abstract: Large dams often alter flow and thermal regimes downstream, resulting in fish spawning delays and larval abundance declines. Accurate prediction of the delayed spawning period under changed thermal regime is critical for selecting a correct timing to modify dam operation and to release the environmental flow needed to enhance fish spawning. We used correlation analysis to investigate the relationship between thermal regime alteration and spawning delay of the four major Chinese carps (FMCC) below the Three Gor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
(46 reference statements)
1
38
0
Order By: Relevance
“…2). Previously, we demonstrated that the delay in observed spawning timing was significantly correlated with decreased water temperature in March, April and May, as well as to the delayed arrival time of 15 and 18°C in spring (Wang et al, 2014). Moreover, with the primary spawning period being dramatically shortened since TGR operation, timing of flow increase was identified as the most significant factor.…”
Section: Reasons For the Variation In Significant Environmental Factorsmentioning
confidence: 83%
See 2 more Smart Citations
“…2). Previously, we demonstrated that the delay in observed spawning timing was significantly correlated with decreased water temperature in March, April and May, as well as to the delayed arrival time of 15 and 18°C in spring (Wang et al, 2014). Moreover, with the primary spawning period being dramatically shortened since TGR operation, timing of flow increase was identified as the most significant factor.…”
Section: Reasons For the Variation In Significant Environmental Factorsmentioning
confidence: 83%
“…). Previously, we demonstrated that the delay in observed spawning timing was significantly correlated with decreased water temperature in March, April and May, as well as to the delayed arrival time of 15 and 18 °C in spring (Wang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the lower abundance and later occurrence of B. superciliaris eggs at YB than at ZY could be due to the negative impacts of discharge control and hypolimnetic and clean water discharge from the XJD. Negative impacts of hypolimnetic and clean water discharge from dams on fish populations have been documented in many river systems (Clarkson & Childs, ; Koehn & Harrington, ; Normando et al, ; Song et al, ; Wang et al, ; Zhong & Power, ). Hypolimnetic discharge from the Garrison Dam in the Missouri River delayed spawning and reduced the larval abundance of Catostomidae species downstream (Wolf, Willis, & Power, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Three Gorges Reservoir (TGR) of China is one of the largest water resource projects in the world. The TGR is of great importance in flood control, hydropower generation, navigation improvement, and ecosystem protection (Wang et al, ). Xiangxi Bay (XXB) is a typical tributary bay of the TGR (Figure ).…”
Section: Introductionmentioning
confidence: 99%